Interference of Illusory Contour Perception by a Distractor - Yang, Junkai; Sui, Lisen; Wu, Hongyuan; Wu, Qian; Mei, Xiaolin; Wu, Xiang (Frontiers in Psychology, 2021)
The visual system is capable of recognizing objects when object information is widely separated in space as revealed by the Kanizsa-type illusory contours. Attentional involvement in perception of illusory contours is an important topic, and the present study examined whether and how the processing of illusory contours is interfered by a distractor. Discrimination between thin and short deformations of an illusory circle was investigated in the absence or presence of a central dynamic patch, with difficulty of discrimination varied in three levels (easy, medium, and hard). Reaction time was significantly shorter in the absence compared to the presence of the distractor in the easy and medium conditions. Correct rate was significantly higher in the absence compared to the presence of the distractor in the easy condition, and the magnitude of the difference between correct rates of distracted and non-distracted responses significantly reduced as task difficulty increased. These results suggested that perception of illusory contours is more likely to be vulnerable to distraction when more attentional resources remain available. The present finding supports that attention is engaged in perception of illusory contours and that distraction of illusory contour processing is associated with perceptual load.